ARGUMEN FILOSOFIS INTEGRASI ILMU DAN AGAMA Perspektif Pemikiran Mullâ Sadrâ - Kuswanjono, Arqom (Jurnal Filsafat "WISDOM", 2007)
The problem of relationship between science and religion emerged in the first time at the Middle Ages, when the controversy about the center of universe occurred between scientists and theologians, that were geocentric view and heliocentric view. It was the starting point of the discourse of relationship between science and religion academically. Than, the discourse of the relationship develop in four types i.e. conflict, independence, dialogue and integration. The concept of integration between science and religion in philosophy of Mullâ Shadrâ perspective is an holistic integration which is built upon the unity of ontology, epistemology and axiology. Ontologically, the relationship is interdependent- integration, it means that science and religion dependent each other. There is no science without religion and there is no religion without science. Epistemologically, the relationship is complementary-integration; it means that all methods which are applied in science and religion (sense experience, reason, intuition and revelation) synergically used to find out the truth. Axiologically, the relationship is qualificative-integration, it means that all values (truth, goodness, beauty and Divineness) qualify each other. Science is not value free; science is not only related to the truth, but also to goodness, beauty and Divineness values.